CMDIfication process for textbook resources. (2nd July 2020) - Fallucchi, Francesca; Luca, Ernesto William De
Interoperability between heterogeneous resources and services is the key to a correctly functioning digital infrastructure, which can provide shared resources at once. We analyse the establishment of a standardised common infrastructure covering metadata, content, and inferred knowledge to allow collaborative work between researchers in the humanities. In this paper, we discuss how to provide a CMDI (Component MetaData Infrastructure) profile for textbooks, in order to integrate it into the Common Language Resources and Technology Infrastructure (CLARIN) and thus to make the data available in an open way and according to the FAIR principles. We focus on the 'CMDIfication' process, which fulfils the needs of our related projects. We describe a process of building resources using CMDI description from Text Encoding Initiative (TEI), Metadata Encoding and Transmission Standard (METS) and Dublin Core (DC) metadata, testing it on the textbook resources of the Georg Eckert Institute (GEI).